Dark Speech : the Performance of Law in Early Ireland. - Stacey, Robin Chapman (Middle Ages series., 2016)
In Dark Speech, Robin Chapman Stacey explores the fascinating interaction between performance and law in Ireland between the seventh and ninth centuries.